Avaliação da atividade inibidora do sistema complemento humano pelo extrato de glândula salivar e conteúdo intestinal de Aedes aegypti (Diptera: Culicidae) - Adalberto Alves Pereira Filho (2018)
Dengue, Chikungunya and Zika are arboviruses transmitted to humans by mosquitoes of the species Aedes (Stegomyia) aegypti (Linnaeus, 1762), causing simultaneous outbreaks with similar clinical manifestations, representing a challenge in the diagnosis and patient treatment. A. aegypti males and females feed on plant-derived sugars but females need a blood meal for egg maturation. In order to obtain blood from vertebrate hosts, haematophagous arthropods need to overcome host hemostasis, represented by vasoconstriction, platelet aggregation and coagulation, as well as inflammation and immune reactions. In this context, molecules present in the saliva and/or intestinal contents of these arthropods may contain inhibitors of the complement system (CS), which is part of the innate immune response to pathogens. CS salivary and intestinal inhibitors are crucial to protect gut cells from haematophagous arthropods against the attack of the complement system present in the ingested blood. Another way to evade complement activation is the uptake of the regulatory protein factor H, also present in serum. Factor H, once deposited in cell surfaces, protects them from complement activation by recruiting the action of the protease called Factor I, thus inactivating the opsonin C3b, also part of the C3 convertases, which will ultimately trigger complement activation and MAC formation. The present work aimed to investigate the anticomplement activity of salivary gland extracts (EGS) and intestinal contents of A. aegypti on the alternative, classical and lectin pathways of the human complement system. In addition, we investigated whether the mosquito's gut is capable of capturing human serum H-factor to protect itself against SC attack. Inhibition of the classical and alternative pathways were evaluated by haemolytic assays and the uptake of factor H by the A. aegypti gut was performed using human anti-factor H antibodies. The results showed that the A. aegypti salivary gland extract was not able to inhibit any of the CS pathways. However, A. aegypti intestinal contents inhibited the classical and the lectin pathways but not the alternative pathway. The intestinal contents did not inhibit the deposition of C1q and MBL components, but inhibited the deposition of downstream components C4b, C3b, C5b and C9. The intestinal content has a serine protease that was able to cleave C4 in bands smaller than 80 kDa. The gut of female A. aegypti was capable of capturing human serum H factor, unlike males. A. aegypti males presented lower survival rate compared to females when these were fed with human blood components (normal human serum and hemoglobin). The C3 molecules in recently blood fed A. aegypti females remain in their original state, becoming inactivated to iC3b as soon as 30 minutes after the blood feed, suggesting that this strategy against complement damage is present in A. aegypti. Considering that human complement inhibitors are vital for the survival of female Aedes mosquitoes, vaccine candidates based on A. aegypti proteins that inhibit human complement have great potential to interfere in aspects related to their survival and reproduction.